Political Rights of Ex-Corruption Convicts in Elections - Zerelda Azzahra Fitrazia; A. Bakir Ihsan; Bilal Iqbal (Jurnal Ilmu Sosial Indonesia (JISI), 2023)
Abstract. This research aims to determine the birth process, the dynamics of the formulation, and the impact of the licensing policy for ex-corruption convicts to participate in elections. By using qualitative research methods and public policy theory, political elites, and corruption, this study found that the licensing policy for ex-corruption convicts in elections is a political process on the basis of providing opportunities for ex-corruption convicts as part of human rights which is then set forth in Law Number 7 of 2017 as a legal decree. Therefore, General Election Commission Regulation (PKPU) Number 20 of 2018 which prohibits ex-corruption convicts from becoming election participants is in itself considered deviant. This policy reaped a lot of controversy and rejection from society, but on the pretext of providing opportunities and fulfilling human rights, the political process came to a decision to be legalized through law. As a result, in the midst of public knowledge about the limited track record of politicians and the attitude of the people towards non-corruption which tends to be permissive, legislative candidates with backgrounds of corruption convicts have emerged and some have been elected in political contests at both the local and national levels. Keywords: Political rights, Ex-Corruption Convicts, Elections, Public Policy, Political Elite. Abstrak. Penelitian ini bertujuan untuk mengetahui proses lahir, dinamika perumusan, dan dampak kebijakan perizinan mantan narapidana korupsi ikut serta dalam pemilu. Dengan menggunakan metode penelitian kualitatif dan teori kebijakan publik, elite politik, dan korupsi, penelitian ini menemukan bahwa kebijakan perizinan mantan narapidana korupsi dalam pemilu merupakan proses politik atas dasar pemberian kesempatan mantan narapidana korupsi sebagai bagian dari hak asasi manusia yang kemudian dituangkan dalam UU No. 7 Tahun 2017. Oleh sebab itu, Peraturan KPU (PKPU) Nomor 20 Tahun 2018 yang melarang mantan narapidana korupsi menjadi peserta pemilu dengan sendirinya dianggap menyimpang. Kebijakan ini menuai banyak kotroversi dan penolakan dari masyarakat, namun atas dalih pemberian kesempatan dan pemenuhan HAM, maka proses politik sampai pada keputusan untuk dilegalisasi melalui undang-undang. Dampaknya, di tengah pengetahuan masyarakat tentang track record politisi yang terbatas dan sikap masyarakat terhadap tindak korupsi yang cenderung permisif, maka bermunculan calon-calon legislatif berlatar belakang narapidana korupsi dan sebagian terpilih dalam kontestasi politik baik pada tingkat lokal maupun nasional. Kata Kunci: Hak politik, Mantan Narapidana Korupsi, Pemilu, Kebijakan Publik, Elite Politik.